Clinical outcomes and survival analysis in patients with psycho-cardiological disease: a retrospective analysis of 132 cases. Issue 3 (March 2021) - Lai, Minhua; Shen, Teimei; Cui, Hong; Lin, Lixia; Ran, Peng; Huo, Peixia; Chen, Ling; Li, Jingzhi
Objectives: The deleterious effects of psychological problems on coronary heart disease (CHD) are not satisfactorily explained. We explored influential factors associated with mortality in psycho-cardiological disease in a Chinese sample. Methods: Of 7460 cardiac patients, we selected 132 patients with CHD and mental illness. Follow-up was conducted via telephone. We analyzed clinical characteristics, clinical outcomes, and survival. Results: The clinical detection rate of psycho-cardiological disease in the overall patient population was 1.8%. Of these, 113 patients completed follow-up; 18 died owing to cardiovascular diseases during follow-up. Kaplan–Meier analysis showed dysphagia, limb function, self-care ability, percutaneous coronary intervention, low-density lipoprotein, total cholesterol, pro-brain natriuretic peptide and high-sensitivity (hs) troponin T had significant associations with cumulative survival. Cox regression analysis showed total cholesterol (hazard ratio [HR]: 2.765, 95% confidence interval [CI]: 1.001–7.641), hs troponin T (HR: 4.668, 95% CI: 1.293–16.854), and percutaneous coronary intervention (HR: 3.619, 95% CI: 1.383–9.474) were independently associated with cumulative survival. Conclusions: The clinical detection rate of psycho-cardiological disease was far lower than expected. Normal total cholesterol and hs troponin T were associated with reduced cardiovascular disease mortality over 2 years. Percutaneous coronary intervention is a prognostic risk factor in patients with psycho-cardiological disease.